The European network for care of children with paediatric rheumatic diseases: care across borders. (21st January 2019) - Dolezalova, Pavla; Anton, Jordi; Avcin, Tadej; Beresford, Michael W; Brogan, Paul A; Constantin, Tamas; Egert, Yona; Foeldvari, Ivan; Foster, Helen E; Hentgen, Veronique; Kone-Paut, Isabelle; Kuemmerle-Deschner, Jasmine B; et al.
Abstract: Objectives: To provide an overview of the paediatric rheumatology (PR) services in Europe, describe current delivery of care and training, set standards for care, identify unmet needs and inform future specialist service provision. Methods: An online survey was developed and presented to national coordinating centres of the Paediatric Rheumatology International Trials Organisation (PRINTO) (country survey) and to individual PR centres (centre and disease surveys) as a part of the European Union (EU) Single Hub and Access point for paediatric Rheumatology in Europe project. The survey contained components covering the organization of PR care, composition of teams, education, health care and research facilities and assessment of needs. Results: Response rates were 29/35 (83%) for country surveys and 164/288 (57%) for centre surveys. Across the EU, approximately one paediatric rheumatologist is available per million population. In all EU member states there is good access to specialist care and medications, although biologic drug availability is worse in Eastern European countries. PR education is widely available for physicians but is insufficient for allied health professionals. The ability to participate in clinical trials is generally high. Important gaps were identified, including lack of standardized clinical guidelines/recommendations and insufficient adolescent transition management planning. Conclusion: This study provides a comprehensive description of current specialist PR service provision across Europe and did not reveal any major differences between EU member states. Rarity, chronicity and complexity of diseases are major challenges to PR care. Future work should facilitate the development, dissemination and implementation of standards of care, treatment and service recommendations to further improve patient-centred health care across Europe.